Chemical and mineral composition of altered volcanic ash in the Early Cretaceous coals of the Kharanorskoe deposit, Eastern Siberia, Russia; Acta Geochimica; Vol. 44, iss. 3 - Vergunov A. V. Aleksey Viktorovich; Arbuzov S. I. Sergey Ivanovich; Kholodov A. S. Aleksey Sergeevich; Novoselov A. A. Andrey Andreevich; Deeva E. S. Elena Sergeevna; Shadrina S. S. Sofjya Sergeevna; Kenesbayev (Kenesbaev) B. K. Bakhtiyar Kairatovich (2025, 2025)
Title screen